Analysis of oral health education actions and strategies as health promotion during pregnancy: an integrative review (Research, Society and Development, 2022)
Objective: to analyze the scientific publications being presented as health education actions and strategies that are in the proposal phase or that have already obtained results on oral prenatal dental care with Brazilian women within the scope of the Unified Health System. Methods: This is an integrated literature, primary sources of data were reviewed, Library through bibliographic data collection in virtual databases (Google Scholar and Scientific Electronic Library Online (SELO). Studies were included that were included in the original study proposals for health improvement and were excluded from the oral assessment, systematic reviews, reviews of literature reviews. Results: Among the 400 findings and after using filters, reading titles and abstracts, 14 studies were used to compose a review. Discussion: Dental exercises in health consultation are the main ones: Brushing exercises during pregnancy, and guidance on orientation, brushing and flossing. Final considerations: a comprehensive analysis on health studies oral and basic education demonstrates that studies are being designed for professional pregnant women permeated by the changes of the SUS at the time of the baby. However, in relation to access to oral health actions for pregnant women, a certain difficulty was seen. Observe yourself still has a certain pregnancy regarding dental care during the gestational period.